1998
DOI: 10.1007/s002210050519
|View full text |Cite
|
Sign up to set email alerts
|

Damping of the wrist joint during voluntary movement

Abstract: Damping characteristics of the musculoskeletal system were investigated during rapid voluntary wrist flexion movements. Oscillations about the final position were induced by introducing a load with the characteristics of negative damping, which artificially reduced the damping of the wrist. Subjects responded to increases in the negatively damped load by stronger cocontraction of wrist flexor and extensor muscles during the stabilization phase of the movement. However, their ability to counteract the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 0 publications
9
54
0
Order By: Relevance
“…With an increase in displacement amplitude from 0.4° to 6° RMS (0.2% to 3% of FCR muscle Insert Figure 6 here length), the stiffness decreased by 31%, the viscosity decreased by 73%, the damping ratio decreased by 71% and the resonant frequency decreased from 10.5 Hz to 7.3 Hz. The changes were consistent with previous findings that both joint stiffness and viscosity decrease with increasing amplitude (Kearney and Hunter, 1982;Milner and Cloutier, 1998;Nichols, 1985).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…With an increase in displacement amplitude from 0.4° to 6° RMS (0.2% to 3% of FCR muscle Insert Figure 6 here length), the stiffness decreased by 31%, the viscosity decreased by 73%, the damping ratio decreased by 71% and the resonant frequency decreased from 10.5 Hz to 7.3 Hz. The changes were consistent with previous findings that both joint stiffness and viscosity decrease with increasing amplitude (Kearney and Hunter, 1982;Milner and Cloutier, 1998;Nichols, 1985).…”
Section: Discussionsupporting
confidence: 92%
“…Milner and Cloutier (1993) determined wrist stiffness coefficients between 3.8 and 16 Nm.rad -1 and viscosity between 0 and 0.11 Nm.s.rad -1 at 15%MVC flexion for various oscillation amplitudes. In a later study, these workers reported damping coefficients at the wrist in the range of 0.06-0.075 Nm.s.rad -1 during voluntary movement (Milner and Cloutier, 1998). In the current study at 15%MVC, the wrist stiffness coefficients ranged between 2.63 and 16.44 Nm.rad -1 and damping coefficients ranged between 0.02 and 0.19 Nm.s.rad -1 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The measured moment of inertia of the wrist and manipulandum during stabilization of a wrist targeted movement ranges from 0.00322 to 0.00541 kgm 2 with an average of 0.00469 kgm 2 (Grey 1997). A similar value was also reported in Milner and Cloutier (1998). Although the viscosity and stiffness of the wrist still remain to be fully measured, the natural viscosity of the relaxed wrist was estimated to be 0.02-0.03 Nms/rad (Gielen and Houk 1984), consistent with the average viscosity of 0.03 Nms/rad estimated in the above stabilization study (Grey 1997).…”
Section: Optimal Control Modelsupporting
confidence: 87%